Coordinated Admissions Program - Andrews, Rodney J. (American Economic Review, 2016)
In the wake of challenges to affirmative action, access to oversubscribed elite public universities remains a contentious issue. Much of the research on these issues focuses on freshman admissions. This paper examines the University of Texas at Austin's Coordinated Admissions Program which offers Texas residents that were not admitted to the University of Texas at Austin as freshman the option of transferring from a participating University of Texas System school. Using the regression discontinuity design, I show that this path to an elite public university has an impact on academic outcomes.